2021
DOI: 10.1186/s12876-021-02071-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of FIB-4 index and clinical outcomes in critically ill patients with acute kidney injury: a cohort study

Abstract: Background The relationship between fibrosis-4 (FIB-4) index and clinical outcomes in patients with acute kidney injury (AKI) is unclear. We aimed to investigate the association between FIB-4 index and all-cause mortality in critically ill patients with AKI. Methods We used data from the Multiparameter Intelligent Monitoring in Intensive Care III (MIMIC-III) database (v1.4). The FIB-4 score was calculated using the existing formulas. logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…[21] Moreover, a recently published study by Shi et al demonstrated that the FIB-4 is also associated with clinical outcomes in critically ill patients with acute kidney injury. [22] Our current study expands the existing literature, which focuses primarily on the predictive ability of FIB-4 regarding liver-related outcomes by demonstrating a mild association between a higher FIB-4 and key extrahepatic events such as renal failure as a composite endpoint and chronic renal failure. Although the association between a higher FIB-4 and the development of renal failure was comparably weak, the results are strengthened by a clear risk increase for renal failure in patients with a higher FIB-4.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…[21] Moreover, a recently published study by Shi et al demonstrated that the FIB-4 is also associated with clinical outcomes in critically ill patients with acute kidney injury. [22] Our current study expands the existing literature, which focuses primarily on the predictive ability of FIB-4 regarding liver-related outcomes by demonstrating a mild association between a higher FIB-4 and key extrahepatic events such as renal failure as a composite endpoint and chronic renal failure. Although the association between a higher FIB-4 and the development of renal failure was comparably weak, the results are strengthened by a clear risk increase for renal failure in patients with a higher FIB-4.…”
Section: Discussionsupporting
confidence: 54%
“…[ 21 ] Moreover, a recently published study by Shi et al demonstrated that the FIB‐4 is also associated with clinical outcomes in critically ill patients with acute kidney injury. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another multicenter prospective study of patients with stable CAD undergoing elective PCI also concluded that elevated FIB-4 and AAR values were independently associated with cardiovascular death, non-fatal MI, and ischemic stroke; however, these correlations were not observed in high APRI and Forns score groups. 34 Additionally, Shi et al 35 have indicated that higher levels of FIB-4 were significantly associated with increased risks of in-hospital, 28-day, and 90-day mortality. More importantly, elevated LFSs have even been identified as independent risk factors for AKI in patients with coronavirus disease 2019 (COVID-19).…”
Section: Discussionmentioning
confidence: 99%